PUBLIC AFFAIRS MANAGEMENT PLAN PROGRESS REPORT FEBRUARY 1988 (Tufts Archival Research Center, 2007)
Confidential; Progress report for the Tobacco Institutes Public Affairs Management Plan in February 1988. Lists several issues pertaining to the tobacco industry, such as excise taxes, Media relations, and Accidental Fires among many others. Contains an overview of each subject, followed by the highlights and a list of next month's goals. Finishes with a chart of the budget for this particular area of concern.